2013
DOI: 10.3340/jkns.2013.54.4.323
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Perioperative Complications Associated with Lumbar Spinal Fusion Surgery, Focusing on Geriatric Patients in the Republic of Korea

Abstract: ObjectiveThe purpose of this study was to examine the efficacy and perioperative complications associated with lumbar spinal fusion surgery, focusing on geriatric patients in the Republic of Korea.MethodsWe retrospectively investigated 485 patients with degenerative spinal diseases who had lumbar spinal fusion surgeries between March 2006 and December 2010 at our institution. Age, sex, comorbidity, American Society of Anesthesiologists (ASA) class, fusion segments, perioperative complications, and outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…4,5,23,24 Studies on patient-rated outcome in older and geriatric patients are rare, often lack a comparison with a control group, and involve only a small number of patients; however, in good agreement with our findings, the majority report that older patients (>70 years of age) benefit as much from lumbar spinal fusion as do younger patients. 7,[24][25][26] Okuda et al 7 compared 31 patients older than 70 years of age with 70 patients younger than 70 years of age and found that elderly patients demonstrated satisfactory clinical and radiographic results, similar to those in younger patients. Acosta et al 26 found perioperative events, intermediate-term clinical outcomes (mean follow-up of 19 months), and fusion rates after multilevel 3608 lumbar fusion in the elderly (>65 years, n ¼ 30) comparable with those of younger patients (<65 years, n ¼ 43).…”
Section: Discussionsupporting
confidence: 92%
“…4,5,23,24 Studies on patient-rated outcome in older and geriatric patients are rare, often lack a comparison with a control group, and involve only a small number of patients; however, in good agreement with our findings, the majority report that older patients (>70 years of age) benefit as much from lumbar spinal fusion as do younger patients. 7,[24][25][26] Okuda et al 7 compared 31 patients older than 70 years of age with 70 patients younger than 70 years of age and found that elderly patients demonstrated satisfactory clinical and radiographic results, similar to those in younger patients. Acosta et al 26 found perioperative events, intermediate-term clinical outcomes (mean follow-up of 19 months), and fusion rates after multilevel 3608 lumbar fusion in the elderly (>65 years, n ¼ 30) comparable with those of younger patients (<65 years, n ¼ 43).…”
Section: Discussionsupporting
confidence: 92%
“…Three-dimensional reconstructions of the micro-CT data demonstrated poor bone regeneration in sites treated with BGM aged (grey; Fig. 6H), in agreement with similar data from elderly patients undergoing spine fusion [65,66]. In contrast, sites treated with BGM WNT showed evidence of robust bone formation and fusion of the transverse processes (blue; Fig.…”
Section: L-wnt3a Activates Stem Cells In Bgm Aged and Improves Bone Gsupporting
confidence: 81%
“…Most previous studies on posterior lumbar interbody fusion in elderly patients have focused on complication rates and, to a lesser extent, on clinical results 4,5,23,24 . Reports on patient-rated outcome in older and geriatric patients are rare, often lack a comparison with a control group, and involve only a small number of patients.…”
Section: Patient Rated Outcomesmentioning
confidence: 99%